Erythropoietin Restores Motor Functions through Angiogenesis in the Thalamus Area of Ischemic Stroke in Rats - Lina, Rifda Naufa; Rahmadi, Mahardian; Khotib, Junaidi (Folia Medica Indonesiana, 2018)
The present study aimed to determine the potency of erythropoietin as angiogenesis inducer in ischemic stroke rats model. Animal model was treated by right unilateral common carotid artery occlusion (rUCCAO) for 90 minutes. The stroke model produced decreased motor function. Eight to 12 week-old Wistar rats were used. rHuEPO was administered for 7 days, starting at 24 hours after stroke induction. Motor functions were measured before and 1, 3 and 7 days after rUCCAO. Whereas, histological damage and VEGF expression were evaluated at day 14. The results showed that rHuEPO significantly increased motor function on day 7, reduced the number of damaged body cell and increased VEGF expression in the thalamus area on day 14. As a conclusion, rHuEPO may restore the motoric function and prevent brain neuronal death by inducing angiogenesis through the increase in the expression of VEGF in rUCCAO-induced ischemic stroke model.